Odpowiedzi

2010-02-03T13:00:54+01:00
F(x)=-x2-4x+1=(3√2)²-4*(3√2-2)+1=(9*2+2)-12√2+8+1=20-12√2+8+1=29-12√2=17√2
2010-02-03T13:01:45+01:00
F(x)= -x²-4x + 1

dla x=3√2 - 2

f(3√2 - 2)=-(3√2 - 2)²-4(3√2 - 2) + 1
f(3√2 - 2)=-(18-12√2+4)-12√2+8+1
f(3√2 - 2)=-18+12√2-4-12√2+9
f(3√2 - 2)=-13

Odp:Wartość funkcji f(x)= -x²-4x + 1 dla x=3√2 - 2 wynosi -13.
2010-02-03T13:10:16+01:00
F(x)= -x²-4x + 1 dla x=3√2 - 2

f(3√2 - 2)=-(3√2 - 2)²-4•(3√2 - 2)+1=-(9√4-12√2+4)-12√2+8+1=
=-9√4+12√2-4-12√2+9=-9•2-4+9=-18-4+9=-22+9=-13

(3√2 - 2)²=(3√2)²-2•3√2•2+(2)²=9√4-12√2+4

(a-b)²=a²-2ab+b²

Odp: Wartość funkcji f(x)= -x²-4x + 1 dla x=3√2 - 2 jest równa -13,
y=-13.